Pentingnya Kolaborasi Orang Tua dan Guru dalam Meningkatkan Literasi Baca dan Tulis Anak-Anak - Sari, Ni Putu Ayu Eka; Apriyanti, Ni Made Leny; Dewi, Ni Putu Anik Kania; Artini, Ni Nengah Nopi; Putri, Ni Nyoman Adelia; Pratiwi, Ni Made Teja; Werang, Basilius Redan (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2024)
This study aims to explore the factors influencing children's literacy at SD Negeri 3 Kubutambahan. Through observation and qualitative data analysis, the research highlights the crucial role of collaboration between parents and teachers in enhancing literacy, as well as the diversity of literacy programs and activities at the school. Despite facing challenges such as resource limitations, the school has identified potential solutions, including strengthening cooperation with the local community and utilizing educational technology. A stimulating school environment also plays a significant role in increasing students' interest in learning. It was found that active parental involvement is key to ensuring the success of literacy improvement efforts. Furthermore, the research concludes that efforts to enhance children's literacy require active involvement from various parties, including parents, teachers, and the community. Close collaboration among all parties is essential in creating a supportive and competitive learning environment. This study provides an in-depth understanding of the challenges and potential solutions in improving children's literacy at SD Negeri 3 Kubutambahan. It lays the foundation for the development of more effective and sustainable strategies in the future.